Exploring the influence of team dynamics and communication relating to infection care, on team reasoning in the ICU using sociograms - Ms Candice Bonaconsa; Associate Professor Esmita Charani; Dr Dena Van den Bergh; Professor Marc Mendelson; Professor Ivan Joubert (International Journal of Infectious Diseases)
Background/Introduction: Team reasoning within multidisciplinary teams (MDTs) to discuss, deliberate, and plan patient care on ward rounds (WRs) is complex. Whilst effective communication targeting specific team members using structured approaches can optimise discussions and decision-making, its sustained implementation across MDTs is challenging. Using visual maps, we explore the influence of team dynamics and communication on group reasoning and the uptake of clinical decisions on intensive care unit (ICU) MDT WRs. Method: Data were collected through observations of WRs in two ICUs at a tertiary hospital in Cape Town, South Africa. Field notes detailed contextual descriptions, team activities, and interactions during patient discussions, and sociograms mapped and quantified episodes of communication. Qualitative data underwent thematic analysis, while descriptive statistics were used for quantitation. Results: Data were gathered from 51 hours of WR observations, including 273 individual patient discussions. Thirty-eight sociograms yielded 1900 communication episodes. Consultants (821/1900,43%) and registrars (835/1900,44%) initiate discussions. Registrars are consistent in delivering a structured update (679/1900,36%) with infection care for every patient. Group reasoning on infection-related care constitutes almost one-third of the overall patient discussion. Nurses, pharmacists, and microbiologist with active roles in infection prevention, antimicrobial stewardship and patient care contribute to 5% (104/1900) of the overall patient discussion and 6% (35/542) specifically to infection care. Among them, microbiologists contribute 92% of inputs to group reasoning on infection care despite attending less than one fifth of discussions.Nineteen percent (368/1900) of discussions involve planning patient care, led to 54% requiring clinical action. Directed and clear communication to registrars and nurses resulted in 79% (159/199) of actions documented, while the reverse was true of undirected and unclear communication, which led to 77% of tasks going undocumented. Ninety three percent (43/45) of infection-related actions are communicated clearly and directly. Team factors (position around patient bedside, side discussions, smartphone use) and interruptions during ward rounds impacts communication clarity and group focus. Discussion: Constructing and effectively communicating a treatment plan is one of the primary purposes of MDT patient discussions. The accurate uptake of key actions by registrars and nurses is dependent on how the task is communicated. Unclear and undirected decisions can be harder for nurses and registrars to interpret and cause delays in care. Quantifying contributions shows how the different categories interact with each other and illustrates the distribution of power and influences during WR discussion. Conclusion: Focusing on optimising team communication that considers all role players can lead to better team dynamics and patient outcomes. Effective uptake of actionable tasks relies on clear and directed communication.